Teratorn and Its Related Elements - a Novel Group of Herpesviruses Widespread in Teleost Genomes - Inoue, Yusuke; Takeda, Hiroyuki (Zoological science, 2023)
Herpesviruses are a large family of DNA viruses infecting vertebrates and invertebrates, and are important pathogens in the field of aquaculture. In general, herpesviruses do not have the ability to integrate into the host genomes since they do not have a chromosomal integration step in their life cycles. Recently, we identified a novel group of herpesviruses, " " and its related elements, in the genomes of various teleost fish species. At least some of the -like herpesviruses are fused with a -like DNA transposon, suggesting that they have acquired the transposon-like intragenomic lifestyle by hijacking the transposon system. In this review, we describe the sequence characteristics of -like herpesviruses and phylogenetic relationships with other herpesviruses. Then we discuss the process of transposon-herpesvirus fusion, their life cycle, and the generality of transposon-virus fusion. -like herpesviruses provide a piece of concrete evidence that even non-retroviral elements can become intragenomic parasites retaining replication capacity, by acquiring transposition machinery from other sources.